Heresy, forgery, novelty condemning, denying, and asserting innovation in ancient Judaism - Klawans, Jonathan (New York Oxford University Press, 2019)
Heresies, forgeries, novelties -- Heresy without orthodoxy: Josephus and the rabbis on dangerous beliefs -- Secret supersessionism? Intimations of novelty concealed at Qumran -- Innovation asserted: the novelties of early Christianity.
Includes bibliographical references
Keywords: Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Jews -- History -- 168 B.C.-135 A.D; Judaism -- Relations -- Christianity; Christianity and other religions; Rabbinical literature -- History and criticism